2010
DOI: 10.2166/wst.2010.510
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking energy consumption in municipal wastewater treatment plants in Japan

Abstract: Reduction of greenhouse gas (GHG) emissions is one of the most important tasks facing municipal WWTPs. Electric power consumption typically accounts for about 90% of the total energy consumption. This study presents a benchmarking analysis of electric power consumption. The specific power consumption (SPC) ranged from 0.44 to 2.07 kWh/m(3) for oxidation ditch plants and from 0.30 to 1.89 kWh/m(3) for conventional activated sludge plants without sludge incineration. Observed differences of the SPC can be attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(67 citation statements)
references
References 4 publications
3
57
1
2
Order By: Relevance
“…Primary wastewater treatment typically focuses on the physical removal of solids and is therefore less energy intensive (0.003-0.37 kWh/m 3 ) compared with other treatment procedures [67]. Tertiary treatment is considered an energy intensive procedure for nutrient removal and/or disinfection, with energy demand ranging from 0.40 to 0.50 kWh/m 3 [14] and even reaching 3.74 kWh/m 3 [69]. A study on energy requirements for wastewater treatment systems in Australia and New Zealand reported that the energy intensity doubled between primary and secondary treatment and then doubled again between secondary and tertiary treatment [18].…”
Section: Energy Implications Of Wastewater Treatment Systemsmentioning
confidence: 99%
“…Primary wastewater treatment typically focuses on the physical removal of solids and is therefore less energy intensive (0.003-0.37 kWh/m 3 ) compared with other treatment procedures [67]. Tertiary treatment is considered an energy intensive procedure for nutrient removal and/or disinfection, with energy demand ranging from 0.40 to 0.50 kWh/m 3 [14] and even reaching 3.74 kWh/m 3 [69]. A study on energy requirements for wastewater treatment systems in Australia and New Zealand reported that the energy intensity doubled between primary and secondary treatment and then doubled again between secondary and tertiary treatment [18].…”
Section: Energy Implications Of Wastewater Treatment Systemsmentioning
confidence: 99%
“…Approximately half of influent carbon is converted into fast growing microbiota, and the remaining half is released to the atmosphere through the generation of CO 2 . One of the largest operational costs in wastewater treatment is electricity, and almost half of a treatment plant's entire energy demand is used for aeration (Mizuta and Shimada, 2010). The current emphasis on aerobic biological treatment wastes much of the energy value of the organic matter and maximizes the production of biosolids.…”
Section: Introductionmentioning
confidence: 99%
“…Upper and lower estimates for energy intensities for technologies such as desalination and wastewater reuse are provided. Compare to the CAS system, oxidation ditch (OD) treatment systems have higher energy demands of 0.5-1.0 in Australia, 0.302 in China, or 0.43-2.07 kWh/m 3 in Japan because of longer hydraulic retention time (HRT) and higher energy consumption for higher specific-oxygen demand [84,88,89].…”
Section: Wastewater Treatment and Energymentioning
confidence: 99%